Dynamics of motion of electron in electrical field - Tchaban, Vasil (Видавництво Львівської політехніки, 2020)
Nowadays, the function of the law of interaction of moving charged bodies has been taken over entirely by the theory of relativity, being covered by a pseudo slogan about the inability of Galileo transformations. In contrast, the article adapts Coulomb’s law in the case of moving charges in all possible speeds in the usual three-dimensional Euclidean space and physical time. This takes into account the finite speed of propagation of the electric field and the law of conservation of the charge. On this basis, the dynamics of the free motion of an electron in a non-uniform electric field are simulated. For qualitative and quantitative evaluations of the manifestation of the relativistic effect on the dynamics of motion, the duplicate time functions of velocities and coordinates obtained by classical Coulomb’s law are given. Electromechanical analogies of electric and gravitational fields have been made.
Keywords: Coulomb’s law; Law of conservation of the charge; Relativistic velocity; Finite velocity of propagation of an electric field; Dynamics of motion of a free electron in a non-uniform electric field